Surgical versus conservative treatment for lumbar disc herniation: a prospective cohort study. Issue 12 (21st December 2016) - Gugliotta, Marinella; da Costa, Bruno R; Dabis, Essam; Theiler, Robert; Jüni, Peter; Reichenbach, Stephan; Landolt, Hans; Hasler, Paul
Abstract : Objectives: Evidence comparing the effectiveness of surgical and conservative treatment of symptomatic lumbar disc herniation is controversial. We sought to compare short-term and long-term effectiveness of surgical and conservative treatment in sciatica symptom severity and quality of life in patients with lumbar disc herniation in a routine clinical setting. Methods: A prospective cohort study of a routine clinical practice registry consisting of 370 patients. Outcome measures were the North American Spine Society questionnaire and the 36-Item Short-Form Health Survey to assess patient-reported back pain, physical function, neurogenic symptoms and quality of life. Primary outcomes were back pain at 6 and 12 weeks. Standard open discectomy was assessed versus conservative interventions at 6, 12, 52 and 104 weeks. We filled in missing outcome variable values with multiple imputation, accounted for repeated measures within patients with mixed-effects models and adjusted baseline group differences in relevant prognostic indicators by inverse probability of treatment weighting. Results: Surgical treatment patients reported less back pain at 6 weeks than those receiving conservative therapy (−0.97; 95% CI −1.89 to −0.09), were more likely to report ≥50% decrease in back pain symptoms from baseline to 6 weeks (48% vs 17%, risk difference: 0.34; 95% CI 0.16 to 0.47) and reported less physical function disability at 52 weeks (−3.7; 95% CI −7.4 to −0.1). The other assessments showed minimal between-group differences with CIs, including the null effect. Conclusions: Compared with conservative therapy, surgical treatment provided faster relief from back pain symptoms in patients with lumbar disc herniation, but did not show a benefit over conservative treatment in midterm and long-term follow-up.